Analysis of Student Difficulties in Learning Biology - Hayatul husna; Siska Nerita; Elza Safitri (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
The difficulties experienced by students in the learning process can be seen from internal factors and external factors. Based on the results of interviews and observations, it can be seen in the form of students' difficulties in the learning process, namely a lot of scientific language, less interesting material causing boredom and lack of enthusiasm, lack of focus making it difficult to concentrate. On external factors such as the teacher's teaching methods, lack of attention and motivation from the family, and student learning methods. The purpose of this study was to find out students's difficulties in learning biology. Sampling in this study used a non-probability sampling technique, namely purposive sampling where the total number of students from 4 classes was taken as much as 25% of the total population, so that a sample of 31 students was used as a sample for all students.The instrument used is a questionnaire in the form of a closed statement using a Likert scale and documentation. The data analysis technique used descriptive analysis quantitatively in the form of percentages. Data analysis by using the percentage (%) of student answers. The result of studentlearning difficulties in biology subjects has high category, internal factors with high criteria and the average percentage of external factors with high criteria. It can be concluded that biggest internal factor causing learning difficulties in biology is the factor of fatigue and the biggest external factor is the family factor.